Lembar Kerja Peserta Didik pada Model Problem-Based Learning Berbasis Local Socio-Scientific Issue untuk Meningkatkan Argumentasi Ilmiah Siswa SMP: Analisis Kebutuhan - Ekawati, Selviana; Supeno, Supeno; Asyiah, Iis Nur (Jurnal Ilmiah Global Education, 2025)
Scientific argumentation skills are an essential foundation in science learning, as they help students think critically, express opinions scientifically, and make decisions based on evidence. Unfortunately, this skill has not yet been optimally developed among junior high school students, mainly due to limited opportunities to practise in a supportive classroom environment. This study aims to identify the need for developing Student Worksheets (SW) based on Problem-Based Learning (PBL) integrated with Local Socio-Scientific Issues (LSSI), as an effort to enhance students' scientific argumentation skills. Using a qualitative descriptive approach, this study involved an initial argumentation skills test and a needs survey distributed to science teachers. The results showed that most students still fall into the low category regarding scientific argumentation skills, and many teachers do not yet have teaching tools to support these skills. However, there is significant potential for integrating the SSI-based approach into science education, mainly since teachers are already accustomed to using active methods in topics such as environmental pollution. These findings are an essential foundation for designing contextual and relevant worksheets, enabling students to learn science and become critical thinkers and caring citizens engaged with the issues around them.